Implementation of Business Ethics in Shariah Banking at Bank Syariah Indonesia of Kaliurang Region - Rismanto; Dwi, Lukman; Pratama, Yhoga Heru; Qayyum, Abdul (SMARTINDO, 2024)
Purpose - This study aims to determine the implementation of business ethics in Islamic banking services and the usefulness of business ethics in Islamic banking services. Design/methodology/approach - This research is included in field research. Data collection was carried out through interviews, documentation, and observation. Data analysis techniques were carried out using descriptive analysis methods. The subjects in this study were customers and employees of Bank Syariah Indonesia of Kaliurang Region who were selected using a purposive sampling technique. Findings and Discussion - The study results show that Bank Syariah Indonesia of Kaliurang Region has implemented the principles of Islamic business ethics, namely honesty, equality, justice, and truth. The Bank through its employees has also been able to be friendly, polite, and courteous to customers and stakeholders which largely contributes to customers’ high level of satisfaction with their services, trust in their guarantee of confidentiality and assets safety, while being able to act fairly by providing adequate service regardless of customer status and class, leading to customers loyalty to the bank. Conclusion – Bank Syariah Indonesia of Kaliurang Region has proved to be a good embodiment of bringing the value of business ethics as it is told within the Shariah concept, and it also confirms the theory of business ethics that such a good performance in this department can be highly influential to an institution’s wellness of performance.